Tourism collaboration and partnerships politics, practice and sustainability - Bramwell Bill; Lane Bernard (New Delhi Viva Books, 2006)
The key importance of involving diverse stakeholders in tourism planning and management is increasingly recognized. Collaboration and partnerships are essential ways of achieving this. Researchers and practitioners examine the processes, issues and polit
Keywords: Tourism